Early Film Theories in Italy, 1896-1922 - Mazzei, Luca; Alovisio, Silvio, 1968-; Casetti, Francesco (Book collections on Project MUSE., 2017)
This collection is the first to bring together scholars to explore the ways in which various people and groups in Italian society reacted to the advent of cinema. Looking at the responses of writers, scholars, clergymen, psychologists, philosophers, members of parliament, and more, the pieces collected here from that period show how Italians developed a common language to describe and discuss this invention that quickly exceeded all expectations and transcended existing categories of thought and artistic forms. The result is a close-up picture of a culture in transition, dealing with a 'scandalous' new technology that appeared poised to thoroughly change everyday life.